PTH 1-34 promoted bone formation by regulating iron metabolism in unloading-induced bone loss - Che, Jingmin; Ren, Weihao; Chen, Xin; Wang, Fang; Zhang, Gejing; Shang, Peng (Frontiers in Endocrinology, 2023)
PTH 1-34 (teriparatide) is approved by FDA for the treatment of postmenopausal osteoporosis. Iron overload is a major contributing factor for bone loss induced by unloading. Whether iron metabolism is involved in the regulation of PTH 1-34 on unloading-induced osteoporosis has not yet been reported. Here, we found that PTH 1-34 attenuated bone loss in unloading mice. PTH 1-34 regulated the disturbance of iron metabolism in unloading mice by activating Nrf2 and further promoting hepcidin expression in the liver. In addition, the Nrf2 inhibitor selectively blocked hepcidin expression in the liver of unloading mice, which neutralized the inhibitory effect of PTH 1-34 on bone loss and the recovery of iron metabolism in unloading mice. Finally, we found that PTH 1-34 promoted the differentiation and inhibited apoptosis of osteoblasts by regulating iron metabolism and maintaining redox balance under unloading conditions. Our results suggested that PTH 1-34 promoted bone formation by regulating iron metabolism under unloading conditions.